2013
DOI: 10.1163/15707563-00002402
|View full text |Cite
|
Sign up to set email alerts
|

Morph-specific and sex-specific temperature effects on morphology in the colour polymorphic damselfly Ischnura elegans

Abstract: Colour polymorphic species with extensive ranges often exhibit large-scale geographic patterns of morph frequency variation. Because colour polymorphism is associated with correlated differences in multiple traits, such as thermal performance, a likely proximate explanation for such patterns is morph-specific responses to temperature variation. The colour polymorphic Blue-tailed damselfiy Ischnura elegans exhibits large-scale geographic variation in morph frequencies, but the possibility that temperature is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 59 publications
(65 reference statements)
1
7
0
Order By: Relevance
“…However, studies addressing putative alternative thermal response phenotypes among the different morphs have been equivocal. Abbott () found that cold temperatures during larval development result in larger sizes of androchromes (but not gynochromes, which are already larger than androchromes in Sweden). In contrast, Bouton et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies addressing putative alternative thermal response phenotypes among the different morphs have been equivocal. Abbott () found that cold temperatures during larval development result in larger sizes of androchromes (but not gynochromes, which are already larger than androchromes in Sweden). In contrast, Bouton et al .…”
Section: Methodsmentioning
confidence: 99%
“…Increasing frequencies of gynochromes towards the range limit likely result in part from a slight thermal tolerance advantage that these social environments confer. However, effects of genetic drift and morph and sex differences in larval growth processes in response to novel climates (Gosden et al, 2011;Abbott, 2013) might also contribute to the observed cline reversal. These combined effects during range expansions may thus reverse or counteract the larger-scale geographic cline across Europe, with increasing frequencies of androchromes typically observed at higher latitudes in I. elegans (Hammers & Van Gossum, 2008;Gosden et al, 2011).…”
Section: Gynochrome Cold Tolerancementioning
confidence: 99%
“…In this case, genes governing hormonal regulation are likely candidates to be major effect genes, owing to the potential for pleiotropic effects of hormones on color, behavior, physiology, and life-history traits (Ketterson and Nolan 1992;Sinervo et al 2001;Svensson et al 2002). In female polymorphic damselflies, phenotypic differences between the morphs have been suggested for behavioral responses to mating attempts by males (Robertson 1985;Sirot and Brockmann 2001), microhabitat selection by adults (Van Gossum et al 2001), oviposition site preference (this study), the dispersal ability of adults , fecundity (Gosden and Svensson 2007), egg size (Takahashi and Watanabe 2010c), egg shape (Joop et al 2007), developmental response (Takahashi et al 2011), larval developmental rate Abbott 2013), and the body shape of adults (Abbott and Gosden 2009;Abbott and Svensson 2010). Several of the morphological traits were heritable, and the morphologies, behaviors, and habitat choice of andromorphs were often similar to the males (Robertson 1985;Van Gossum et al 2001;Abbott and Svensson 2010).…”
Section: Genetic Basis and Maintenance Of Resource Partitioningmentioning
confidence: 78%
“…), developmental response (Takahashi et al. ), larval developmental rate (Abbott and Svensson ; Abbott ), and the body shape of adults (Abbott and Gosden ; Abbott and Svensson ). Several of the morphological traits were heritable, and the morphologies, behaviors, and habitat choice of andromorphs were often similar to the males (Robertson ; Van Gossum et al.…”
Section: Discussionmentioning
confidence: 99%
“…The trans generational effects of adult behaviour on the fitness of their progeny have been little studied (Thompson et al 2011). Despite the wide occurrence of female polymorphism in Odonates, few studies have examined the growth and survival of the progeny generated by different female morphs (Abbott and Svensson 2005;Bots et al 2010a;Bouton et al 2011;Abbott 2013). Such studies are important, since fitness will ultimately depend upon selection that operates along successive generations (Stearns 1992).…”
Section: Introductionmentioning
confidence: 99%